Analyzing Thermal Efficiency with Pin Fins, Perforated Bases, SolidWorks 2023 Transient Analysis - Talabani, Serwan S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
A group of fifteen central processing unit (CPU) heat sinks of circular, hexagonal, and rectangular shapes with different f in designs and perforation directions was created and analyzed using SolidWorks 2023. In boundary conditions, a heat flux of 65 W was applied, while the surrounding air was at 25°C, and a heat transfer coefficient of 6 W/m2·K was considered. Perforation caused a weight decrease of up to 67.4% in the heat sinks, while perforation orientations had a greater effect on heat dissipation than perforation size. In heat sinks with vertically perforated pins and base R5, the lowest maximum temperature of 77.5°C, the lowest weight of 412.56 g, and the best heat dissipation occurred.